Normal Probability Distributions - Hauselt Jr, William J (Statistics for Social Science | Top Hat, 2016)
Keywords: dept.psy

Neuroendocrine profiles associated with discrete behavioural variation in Symphodus ocellatus, a species with male alternative reproductive tactics. - Nugent, Bridget M.; Stiver, Kelly A.; Alonzo, Suzanne H.; Hofmann, Hans A. (Molecular Ecology, 2016)
The molecular mechanisms underlying phenotypic plasticity are not well understood. Identifying mechanisms underlying alternative reproductive tactics (ARTs) in species for which the behavioural and fitness consequences of this variation are well characterized provides an opportunity to integrate evolutionary and mechanistic understanding of the maintenance of variation within populations. In the ocellated wrasse Symphodus ocellatus, the behavioural phenotypes of three distinct male morphs (sneakers, satellites and nesting males), which arise from a single genome, have been thoroughly characterized. To determine the neuroendocrine and genomic mechanisms associated with discrete phenotypic variation and ARTs in S. ocellatus in their natural environment, we constructed a whole-brain de novo transcriptome and compared global patterns of gene expression between sexes and male morphs. Next, we quantified circulating cortisol and 11-ketotestosterone (11-kt), mediators of male reproductive behaviours, as well as stress and gonadal steroid hormone receptor expression in the preoptic area, ventral subpallial division of the telencephalon and dorsolateral telencephalon, critical brain regions for social and reproductive behaviours. We found higher levels of 11-kt in nesting males and higher levels of cortisol in sneaker males relative to other male morphs and females. We also identified distinct patterns of brain region-specific hormone receptor expression between males such that most hormone receptors are more highly expressed in satellites and nesting males relative to sneakers and females. Our results establish the neuroendocrine and molecular mechanisms that underlie ARTs in the wild and provide a foundation for experimentally testing hypotheses about the relationship between neuromolecular processes and reproductive success. Copyright © 2016 John Wiley & Sons Ltd.
13 citations (Crossref) [2023-10-31] Citation Key Alias: pop00070 tex.type: [object Object]
Keywords: *Neurosecretory Systems/ph [Physiology]; *Perciformes/ph [Physiology]; *Reproduction; *Sexual Behavior; Animal; 11-ketotestosterone; Animals; Brain; Brain/me [Metabolism]; Female; Hydrocortisone; Hydrocortisone/bl [Blood]; Male; Nesting Behavior; Neurosecretory Systems; Perciformes; Perciformes/ge [Genetics]; Phenotype; Reproduction; Sexual Behavior; Animal; Testosterone; Testosterone/aa [Analogs & Derivatives]; Testosterone/bl [Blood]; Transcriptome; alternative reproductive tactics; analogs and derivatives; animal; blood; brain; dept.psy; female; gene expression; genetics; hormones; hydrocortisone; male; metabolism; nesting; neurosecretion; peer-reviewed; phenotype; physiology; reproduction; sexual behavior; testosterone; transcriptome

Ocean acidification affects fish spawning but not paternity at CO2 seeps - Milazzo, Marco; Cattano, Carlo; Alonzo, Suzanne H; Foggo, Andrew; Gristina, Michele; Rodolfo-Metalpa, Riccardo; Sinopoli, Mauro; Spatafora, Davide; Stiver, Kelly A; Hall-Spencer, Jason M (Proceedings of the Royal Society B: Biological Sciences, 2016)
Fish exhibit impaired sensory function and altered behaviour at levels of ocean acidification expected to occur owing to anthropogenic carbon dioxide emissions during this century. We provide the first evidence of the effects of ocean acidification on reproductive behaviour of fish in the wild. Satellite and sneaker male ocellated wrasse (Symphodus ocellatus) compete to fertilize eggs guarded by dominant nesting males. Key mating behaviours such as dominant male courtship and nest defence did not differ between sites with ambient versus elevated CO2 concentrations. Dominant males did, however, experience significantly lower rates of pair spawning at elevated CO2 levels. Despite the higher risk of sperm competition found at elevated CO2, we also found a trend of lower satellite and sneaker male paternity at elevated CO2 Given the importance of fish for food security and ecosystem stability, this study highlights the need for targeted research into the effects of rising CO2 levels on patterns of reproduction in wild fish. Copyright © 2016 The Author(s).
32 citations (Crossref) [2023-10-31] Place: England Milazzo, Marco. Department of Earth and Marine Sciences (DiSTeM), CoNISMa, University of Palermo, Palermo 90123, Italy marco.milazzo@unipa.it. Cattano, Carlo. Department of Earth and Marine Sciences (DiSTeM), CoNISMa, University of Palermo, Palermo 90123, Italy. Alonzo, Suzanne H. PBSci-Ecology and Evolutionary Biology Department, Institute of Marine Sciences, University of California Santa Cruz, Santa Cruz, CA 95064, USA. Foggo, Andrew. Marine Biology and Ecology Research Centre, Plymouth University, Plymouth, PL4 8AA, UK. Gristina, Michele. CNR-IAMC, Mazara del Vallo (TP), 91026, Italy. Rodolfo-Metalpa, Riccardo. Institut de Recherche pour le Developpement, UMR 250 ENTROPIE, Noumea, 98848, New Caledonia. Sinopoli, Mauro. Institute for Environmental Protection and Research (ISPRA), Palermo 90143, Italy. Spatafora, Davide. Department of Earth and Marine Sciences (DiSTeM), CoNISMa, University of Palermo, Palermo 90123, Italy. Stiver, Kelly A. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. Hall-Spencer, Jason M. Marine Biology and Ecology Research Centre, Plymouth University, Plymouth, PL4 8AA, UK International Educational and Research Laboratory Program, Shimoda Marine Research Center, University of Tsukuba, 5-10-1 Shimoda, Shizuoka 415-0025, Japan.
Keywords: *Carbon Dioxide/ch [Chemistry]; *Perciformes/ph [Physiology]; *Reproduction/ph [Physiology]; *Seawater/ch [Chemistry]; *Sexual Behavior; Animal; Alternative reproductive tactics; Animals; CO2 vent; Carbon Dioxide; Climate change; Hydrogen-Ion Concentration; Labrid; Labridae; Male; Oceans and Seas; Perciformes; Reproduction; Seawater; Sexual Behavior; Animal; Symphodus ocellatus; acidification; animal; anthropogenic effect; carbon dioxide; carbon emission; chemistry; climate change; concentration (composition); courtship; dept.psy; ecological stability; food security; male; pH; paternity; perciform; physiology; reproduction; reproductive behavior; sea; sea water; sexual behavior; spawning population; sperm competition; wild population

Human choices between variable and fixed rewards in hypothetical variable‐delay and double‐reward discounting procedures - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2016)
Prior research has shown that nonhumans show an extreme preference for variable-over fixed-delays to reinforcement. This well-established preference for variability occurs because a reinforcer's strength or “value” decreases according to a curvilinear function as its delay increases. The purpose of the present experiments was to investigate whether this preference for variability occurs with human participants making hypothetical choices. In three experiments, participants recruited from Amazon Mechanical Turk made choices between variable and fixed monetary rewards. In a variable-delay procedure, participants repeatedly chose between a reward delivered either immediately or after a delay (with equal probability) and a reward after a fixed delay (Experiments 1 and 2). In a double-reward procedure, participants made choices between an alternative consisting of two rewards, one delivered immediately and one after a delay, and a second alternative consisting of a single reward delivered after a delay (Experiments 1 and 3). Finally, all participants completed a standard delay-discounting task. Although we observed both curvilinear discounting and magnitude effects in the standard discounting task, we found no consistent evidence of a preference for variability-as predicted by two prominent models of curvilinear discounting (i.e., a simple hyperbola and a hyperboloid)-in our variable-delay and double-reward procedures. This failure to observe a preference for variability may be attributed to the hypothetical, rule-governed nature of choices in the present study. In such contexts, participants may adopt relatively simple strategies for making more complex choices.
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00258 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

A longitudinal follow-up study of happiness and meaning-making - Abe, Jo Ann A. (The Journal of Positive Psychology, 2016)
The long-term outcomes associated with happiness and meaning-making were examined by following up on participants in previous studies on experiential learning an average of 2.5 years later. Measures of happiness and meaning-making were extracted by analyzing the participants' journals using a computerized text-analysis program. Happiness as assessed by a composite measure of positive emotionality showed weak associations with the measures of adaptive functioning, and was negatively correlated with optimism, as well as positively correlated with emotion suppression. By contrast, meaning-making as assessed by composite measures of cognitive processing and self-distancing was robustly positively correlated with almost all measures of adaptive functioning. Regression analyses revealed that the two measures of meaning and their interaction term accounted for 20-24% of the variance in predicting the outcome measures. This study revealed that there may be at times a trade-off between happiness and meaning-making as well as a reversal in their patterns of long-term outcomes.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-977-358-552-036 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: LIWC; dept.psy; follow up; happiness; longitudinal; meaning-making; regression analysis; self-distancing; text-analysis

Ovarian fluid allows directional cryptic female choice despite external fertilization. - Alonzo, Suzanne H; Stiver, Kelly A; Marsh-Rollo, Susan E (Nature Communications, 2016)
In species with internal fertilization, females can favour certain males over others, not only before mating but also within the female's reproductive tract after mating. Here, we ask whether such directional post-mating (that is, cryptic) female mate choice can also occur in species with external fertilization. Using an in vitro sperm competition experiment, we demonstrate that female ovarian fluid (ovarian fluid) changes the outcome of sperm competition by decreasing the importance of sperm number thereby increasing the relative importance of sperm velocity. We further show that ovarian fluid does not differentially affect sperm from alternative male phenotypes, but generally enhances sperm velocity, motility, straightness and chemoattraction. Under natural conditions, female ovarian fluid likely increases the paternity of the preferred parental male phenotype, as these males release fewer but faster sperm. These results imply females have greater control over fertilization and potential to exert selection on males in species with external fertilization than previously thought possible.
81 citations (Crossref) [2023-10-31] Place: England Alonzo, Suzanne H. Department of Ecology and Evolutionary Biology, Yale University, 165 Prospect Street, New Haven, Connecticut 06520, USA. Alonzo, Suzanne H. Department of Ecology and Evolutionary Biology, University of California Santa Cruz, 1156 High Street, Santa Cruz, California 95064, USA. Stiver, Kelly A. Department of Ecology and Evolutionary Biology, Yale University, 165 Prospect Street, New Haven, Connecticut 06520, USA. Stiver, Kelly A. Psychology Department, Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515, USA. Marsh-Rollo, Susan E. Department of Ecology and Evolutionary Biology, University of California Santa Cruz, 1156 High Street, Santa Cruz, California 95064, USA. Marsh-Rollo, Susan E. Department of Psychology, Neuroscience, and Behaviour, McMaster University, 1280 Main Street W, Hamilton, Ontario, Canada L8S4K1.
Keywords: *Body Fluids/me [Metabolism]; *Choice Behavior/ph [Physiology]; *Fertilization/ph [Physiology]; *Ovary/me [Metabolism]; *Spermatozoa/ph [Physiology]; Animals; Body Fluids; Choice Behavior; Female; Fertilization; Male; Ovary; Perciformes; Perciformes/ph [Physiology]; Reproduction; Reproduction/ph [Physiology]; Sexual Behavior; Animal; Sexual Behavior; Animal/ph [Physiology]; Sperm Count; Spermatozoa; animal; body fluid; decision making; dept.psy; experimental study; female; fertilization; fertilization (reproduction); in vitro study; liquid; male; mate choice; metabolism; ovary; paternity; phenotype; physiology; reproduction; sexual behavior; species; sperm; sperm competition; spermatozoon; spermatozoon count; spermatozoon motility; thinking

Age-related effects of chronic restraint stress on ethanol drinking, ethanol-induced sedation, and on basal and stress-induced anxiety response. - Fernandez, Macarena Soledad; Fabio, Maria Carolina; Miranda-Morales, Roberto Sebastian; Virgolini, Miriam B; De Giovanni, Laura N; Hansen, Cristian; Wille-Bille, Aranza; Nizhnikov, Michael E; Spear, Linda P; Pautassi, Ricardo Marcos (Alcohol, 2016)
Adolescents are sensitive to the anxiolytic effect of ethanol, and evidence suggests that they may be more sensitive to stress than adults. Relatively little is known, however, about age-related differences in stress modulation of ethanol drinking or stress modulation of ethanol-induced sedation and hypnosis. We observed that chronic restraint stress transiently exacerbated free-choice ethanol drinking in adolescent, but not in adult, rats. Restraint stress altered exploration patterns of a light-dark box apparatus in adolescents and adults. Stressed animals spent significantly more time in the white area of the maze and made significantly more transfers between compartments than their non-stressed peers. Behavioral response to acute stress, on the other hand, was modulated by prior restraint stress only in adults. Adolescents, unlike adults, exhibited ethanol-induced motor stimulation in an open field. Stress increased the duration of loss of the righting reflex after a high ethanol dose, yet this effect was similar at both ages. Ethanol-induced sleep time was much higher in adult than in adolescent rats, yet stress diminished ethanol-induced sleep time only in adults. The study indicates age-related differences that may increase the risk for initiation and escalation in alcohol drinking. Copyright © 2016 Elsevier Inc. All rights reserved.
27 citations (Crossref) [2023-10-31] Place: United States Fernandez, Macarena Soledad. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina; Center for Development and Behavioral Neuroscience, Binghamton University, Binghamton, NY, USA. Fabio, Maria Carolina. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina; Center for Development and Behavioral Neuroscience, Binghamton University, Binghamton, NY, USA. Miranda-Morales, Roberto Sebastian. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina. Virgolini, Miriam B. Instituto de Farmacologia Experimental de Cordoba (IFEC-CONICET), Cordoba, Argentina; Departamento de Farmacologia, Facultad de Ciencias Quimicas, UNC, Cordoba, Argentina. De Giovanni, Laura N. Instituto de Farmacologia Experimental de Cordoba (IFEC-CONICET), Cordoba, Argentina; Departamento de Farmacologia, Facultad de Ciencias Quimicas, UNC, Cordoba, Argentina. Hansen, Cristian. Laboratorio de Analisis Clinicos Especializados (LACE), Cordoba, Argentina. Wille-Bille, Aranza. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina. Nizhnikov, Michael E. Southern Connecticut State University, New Haven, CT, USA. Spear, Linda P. Center for Development and Behavioral Neuroscience, Binghamton University, Binghamton, NY, USA. Pautassi, Ricardo Marcos. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba (UNC), Cordoba, Argentina. Electronic address: rpautassi@gmail.com.
Keywords: *Alcohol Drinking/px [Psychology]; *Anxiety/px [Psychology]; *Ethanol/ad [Administration & Dosage]; *Hypnotics and Sedatives/ad [Administration & Dosage]; *Stress; Psychological/px [Psychology]; Adolescent; Adult; Age Factors; Alcohol Drinking; Alcohol Drinking/ae [Adverse Effects]; Alcohol Drinking/bl [Blood]; Animals; Anxiety; Anxiety/bl [Blood]; Anxiety/et [Etiology]; Article; Chronic Disease; Ethanol; Ethanol/to [Toxicity]; Hypnotics and Sedatives; Hypnotics and Sedatives/to [Toxicity]; Male; Rat; Rats; Rats; Sprague-Dawley; Rats; Wistar; Restraint stress; Sprague Dawley rat; Stress; Psychological; Stress; Psychological/bl [Blood]; Stress; Psychological/co [Complications]; Wistar rat; acute stress; adverse effects; age; age distribution; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; anxiety; blood; body weight; chronic disease; complication; controlled study; corticosterone; corticosterone blood level; dept.psy; drinking behavior; etiology; hypnosis; hypnotic sedative agent; locomotion; male; mental stress; motor activity; mouse; nonhuman; open field test; peer-reviewed; psychology; rat; restrain stress; righting reflex; sedation; sex difference; sleep time; stimulus response; stress

The role of genes involved in stress, neural plasticity, and brain circuitry in depressive phenotypes: Convergent findings in a mouse model of neglect. - Montalvo-Ortiz, Janitza L; Bordner, Kelly A; Carlyle, Becky C; Gelernter, Joel; Simen, Arthur A; Kaufman, Joan (Behavioural brain research, 2016)
Early life neglect increases risk for the development of psychopathologies during childhood and adulthood, including depression and anxiety disorders. We recently reported epigenetic changes in DNA derived from saliva in three genes predicted depression in a cohort of maltreated children: DNA-binding protein inhibitor ID-3 (ID3), Glutamate NMDA Receptor (GRIN1), and Tubulin Polymerization Promoting Protein (TPPP). To validate the role of these genes in depression risk, secondary analyses were conducted of gene expression data obtained from medial prefrontal cortex (mPFC) tissue of mice subjected to a model of maternal neglect which included maternal separation and early weaning (MSEW). Anxiety and depression-like phenotype data derived using the elevated plus maze (EPM) and forced swimming test (FST), respectively, were also available for secondary analyses. Behavioral tests were conducted in MSEW and control adult male mice when they were between 65 and 80days old. ID3, GRIN1 and TPPP gene expression in the mPFC were found to significantly predict behavioral differences in the EPM and FST. These results further support the role of these genes in the etiology of depressive and anxiety phenotypes following early life stress. Copyright © 2016. Published by Elsevier B.V.
26 citations (Crossref) [2023-10-31] Place: Netherlands Montalvo-Ortiz, Janitza L. Department of Psychiatry, Yale University, New Haven, CT, 06520, United States. Bordner, Kelly A. Southern Connecticut State University, New Haven, CT, United States. Carlyle, Becky C. Department of Psychiatry, Yale University, New Haven, CT, 06520, United States. Gelernter, Joel. Department of Psychiatry, Yale University, New Haven, CT, 06520, United States; Veterans Administration, West Haven, CT, United States. Simen, Arthur A. Neuroscience Research Unit, Pfizer Worldwide Research & Development, Cambridge, MA, United States. Kaufman, Joan. Center for Child and Family Traumatic Stress, Kennedy Krieger Institute, United States; Department of Psychiatry, Johns Hopkins School of Medicine, United States. Electronic address: joan.kaufman@kennedykrieger.org.
Keywords: *Depression/pa [Pathology]; *Gene Expression Regulation/ph [Physiology]; *Maternal Deprivation; *Neuronal Plasticity/ph [Physiology]; *Prefrontal Cortex/me [Metabolism]; *Stress; Psychological/pa [Pathology]; Animals; Article; C57BL mouse; DBA mouse; DNA-binding protein inhibitor ID-3 (ID3); Depression; Disease Models; Animal; GRIN1 gene; Gene Expression Regulation; Glutamate NMDA receptor (GRIN1); Gprin1 protein; mouse; ID3 gene; Idb3 protein; mouse; Inhibitor of Differentiation Proteins; Inhibitor of Differentiation Proteins/ge [Genetics]; Inhibitor of Differentiation Proteins/me [Metabolism]; Male; Maternal Deprivation; Maze Learning; Maze Learning/ph [Physiology]; Methylation; Mice; Mice; Inbred C57BL; Mice; Inbred DBA; Microarray Analysis; Neglect; Nerve Tissue Proteins; Nerve Tissue Proteins/ge [Genetics]; Nerve Tissue Proteins/me [Metabolism]; Neuronal Plasticity; Prefrontal Cortex; RNA; Messenger; RNA; Messenger/me [Metabolism]; Receptors; N-Methyl-D-Aspartate; Receptors; N-Methyl-D-Aspartate/ge [Genetics]; Receptors; N-Methyl-D-Aspartate/me [Metabolism]; Stress; Psychological; Swimming; Swimming/px [Psychology]; TPPP protein; mouse; Tubulin polymerization promoting protein (TPPP); animal; animal experiment; animal model; animal tissue; anxiety; connectome; controlled study; depression; dept.psy; disease activity; disease model; early life stress; gene; gene expression regulation; gene function; gene identification; gene location; genetics; inhibitor of differentiation protein; male; maternal deprivation; maze test; medial prefrontal cortex; mental stress; messenger RNA; metabolism; microarray analysis; molecular dynamics; molecular pathology; mouse; n methyl dextro aspartic acid receptor; nerve cell plasticity; nerve protein; nonhuman; pathology; peer-reviewed; phenotype; physiology; prediction; prefrontal cortex

Transgenerational transmission of the effect of gestational ethanol exposure on ethanol Use‐Related behavior - Nizhnikov, Michael E; Popoola, Daniel O; Cameron, Nicole M (Alcoholism: Clinical and Experimental Research, 2016)
Background: Prenatal alcohol exposure (PAE) enhances the risk for alcoholism by increasing the propensity to consume alcohol and altering neurophysiological response to alcohol challenge. Trans-generationally transmittable genetic alterations have been implicated in these behavioral changes. To date, transgenerational transmission of PAE-induced behavioral responses to alcohol has never been experimentally investigated. Therefore, we explored the transgenerational transmission of PAE-induced behavioral effects across 3 generations. Methods: Pregnant Sprague Dawley dams received 1 g/kg ethanol (EtOH) or water daily on gestational days 17 through 20 via gavage, or remained untreated in their home cages. To produce second filial (F2) or F3 generations, similarly treated adult F1 or F2 offspring were mated and left undisturbed through gestation. On postnatal day (PND) 14, male and female F1, F2, and F3 offspring were tested for consumption of 5% (w/v) EtOH (in water), or water. Using the loss of righting reflex (LORR) paradigm on PND 42, F1 and F2 adolescent male offspring were tested for sensitivity to acute EtOH-induced sedation-hypnosis at 3.5 or 4.5 g/kg dose. F3 male adolescents were similarly tested at 3.5 g/kg dose. Blood EtOH concentration (BEC) was measured at waking. Results: EtOH exposure increased EtOH consumption compared to both water and untreated control groups in all generations. EtOH-treated group F1 and F2 adolescents displayed attenuated LORR duration compared to the water group. No attenuated LORR was observed in the F3 generation. BEC at waking corroborated with the significant LORR duration differences while also revealing differences between untreated control and water groups in F1 and F2 generations. Conclusions: Our results provide novel behavioral evidence attesting that late gestational moderate EtOH exposure increases EtOH intake across 3 generations and may alter sensitivity to EtOH-induced sedation-hypnosis across 2 generations. © 2016 Research Society on Alcoholism.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-977-782-274-445 tex.type: [object Object]
Keywords: Alcohol Drinking; Animals; Animals; Newborn; Article; Ethanol; Female; Infant; Intake; Loss of Righting Reflex; Male; Pregnancy; Prenatal Exposure Delayed Effects; Rat; Rats; Rats; Sprague-Dawley; Sprague Dawley rat; adult; alcohol; alcoholism; animal; animal experiment; behavior; behavior change; chemically induced; dept.psy; drinking behavior; epigenetics; female; genetics; hypnosis; male; newborn; nonhuman; pregnancy; prenatal exposure; priority journal; progeny; psychology; rat; righting reflex; sedation; transgenerational transmission; wakefulness; water